THE IMPLEMENTATION OF RESTORATIVE JUSTICE IN DOMESTIC VIOLENCE CRIMES (A STUDY IN THE TOBA POLICE RESORT JURISDICTION) - Wahyu Indrajaya; Rizkan Zulyadi; Wenggedes Frensh (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research implementation of the Restorative Justice approach in handling domestic violence (KDRT) cases in the Polres Toba jurisdiction. Restorative Justice is a conflict resolution method that emphasizes the restoration of relationships between victims, perpetrators, families, and the community, as an alternative to the formal court process, which tends to be repressive. The research method used is field research with a descriptive case study approach, involving observation, in-depth interviews, and document analysis. The research informants include police officers, particularly from the Women and Children Service Unit (PPA), related legal institutions, victims, and perpetrators. The results show that Restorative Justice in Polres Toba has been successfully implemented by leveraging local wisdom values such as deliberation (musyawarah), the role of traditional leaders, and mutual cooperation (gotong royong), which support a dialogical and participatory mediation and conflict resolution process. This process involves mediation stages facilitated by officers, active involvement of families, and internal regulatory support that provides the legal basis for the implementation of restorative justice. However, the application of Restorative Justice still faces challenges such as limited resources, lack of public understanding, and conflicts between customary values and victim protection. The study concludes that Restorative Justice is an effective alternative for resolving domestic violence cases in Polres Toba by providing fair and humane solutions. This research recommends increasing socialization efforts, training for officers, and strengthening inter-agency coordination to optimize the implementation of Restorative Justice in the future.